Microstructural properties and dielectric relaxations of partially fluorinated copolymers. (21st November 2018) - Soto Puente, Jorge Arturo; Delbreilh, Laurent; Dittmer, Jens; Briand, Valérie; Vernay, Sébastien; Dargent, Eric
Abstract: The aim of this work is to correlate the presence of the pending -CF3 group on the microstructure and the relaxation behavior of the amorphous phase in a fluorinated terpolymer. On this basis, the properties of EFEP (ethylene-tetrafluoroethylene-hexafluoropropylene) are compared to those of ETFE (ethylene-tetrafluoroethylene). For both polymers, the lower hydrophobic character compared to PTFE (polytetrafluoroethylene) is related to the modification of the fluorine sheet-like orientation. Besides, it is noticed that the–CF3 groups create defects in the crystalline phase and thus, decrease the melting temperature and degree of crystallinity in EFEP compared to ETFE. Moreover, the steepness of the main relaxation time evolution with temperature and associated to the amorphous phase is clearly modified. Once again the steric hindrance of –CF3 groups decreases the packing efficiency in EFEP compared to the fluorinated polymers without pending groups. Graphical abstract: Highlights: Pending fluorinated groups modify the crystalline/amorphous arrangements. High ability to crystallize was evidenced for the studied materials. Thermal signature of amorphous phase was only revealed after thermal annealing. Main relaxation process was significantly affected by the voluminous pending group.